2019
DOI: 10.1193/010518eqs001m
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic Pushover Method for Seismic Assessment under Multiple Earthquakes

Abstract: A new method for the seismic performance assessment of structures subjected to a sequence of earthquakes is presented. The method is based on the cyclic pushover analysis of a multi-degree-of-freedom (MDOF) structure. Instead of relying on a single value of target displacement, as in the case of monotonic push-over methods, a simplified cyclic displacement history is derived from an equivalent single-degree-of-freedom (SDOF) structure for the assessment of the MDOF one. The main advantage of the method is that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Similarly, they concluded that the influence of major aftershocks on the damage potential is significant because the energybased damage index of tall RC buildings increases due to the seismic sequences. In addition to these studies, Zhai et al [30][31][32], Di Sarno et al [33][34][35][36], Abdelnaby et al [37][38][39][40][41], Kagermanov and Gee [42,43], Yang et al [44,45], Yaghmaei-Sabegh et al [46], Qiao et al [47], Orlacchio et al [48], Hoveidae and Radpour [49], and Pirooz et al [50] investigated the nonlinear response of building structures under seismic sequences. Although most of those studies were analytical in nature, one experimental study used a shaking table [47].…”
Section: Brief Review Of Related Studies 121 Studies On the Responses...mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, they concluded that the influence of major aftershocks on the damage potential is significant because the energybased damage index of tall RC buildings increases due to the seismic sequences. In addition to these studies, Zhai et al [30][31][32], Di Sarno et al [33][34][35][36], Abdelnaby et al [37][38][39][40][41], Kagermanov and Gee [42,43], Yang et al [44,45], Yaghmaei-Sabegh et al [46], Qiao et al [47], Orlacchio et al [48], Hoveidae and Radpour [49], and Pirooz et al [50] investigated the nonlinear response of building structures under seismic sequences. Although most of those studies were analytical in nature, one experimental study used a shaking table [47].…”
Section: Brief Review Of Related Studies 121 Studies On the Responses...mentioning
confidence: 99%
“…From the author's viewpoint, few studies have investigated the application of the pushover-based procedure using a nonlinear equivalent SDOF model for the seismic evaluation of a building considering seismic sequences; the existing studies are those of Guerrero et al [21], Kagermanov and Gee [42,43], and Orlacchio et al [48]. Such studies are essential in the author's opinion.…”
Section: Brief Review Of Related Studies 121 Studies On the Responses...mentioning
confidence: 99%
“…because the energy-based damage index of tall RC buildings increases due to the seismic sequences. In addition to these studies, Zhai et al [30][31][32][33], Di Sarmo et al [33][34][35][36], Abdelnaby et al [37][38][39][40][41], Kagermanov and Gee [42,43], Yang et al [44,45], Yaghmaei-Sabegh et al [46], Qiao et al [47], Orlacchio et al [48], Hoveidae and Radpour [49], and Pirooz et al [50] investigated the nonlinear response of building structures under seismic sequences. Although most of those studies were analytical in nature, one experimental study used a shaking table [47].…”
Section: Studies On the Responses Of Structures Under Seismic Sequencesmentioning
confidence: 99%
“…Similarly, they had concluded that the influence of major aftershocks on the damage potential is significant because the energy-based damage index of tall RC buildings increases due to the seismic sequences. In addition to these studies, Zhai et al [30][31][32][33], Di Sarno et al [33][34][35][36], Abdelnaby et al [37][38][39][40][41], Kagermanov and Gee [42,43], Yang et al [44,45], Yaghmaei-Sabegh et al [46], Qiao et al [47], Orlacchio et al [48], Hoveidae and Radpour [49], and Pirooz et al [50] investigated the nonlinear response of building structures under seismic sequences. Although most of those studies were analytical in nature, one experimental study used a shaking table [47].…”
Section: Studies On the Responses Of Structures Under Seismic Sequencesmentioning
confidence: 99%